TRADE ROUTES OF THE KHIVA KHANATE AND THEIR CARTOGRAPHIC ANALYSIS (17TH–19TH CENTURIES) (World Bulletin of Social Sciences, 2026)
This article is focused on the topic "Pedagogical foundations of improving the philosophical foundations of the formation of eco-culture in primary school students", and it is important to highlight the development of eco-culture in students from a scientific and pedagogical perspective. The article provides an analysis and suggestions on the philosophical and pedagogical foundations of the concept of eco-culture, as well as effective ways of forming eco-culture in the minds of primary school students.
Keywords: Primary; students; ecoculture; formation